Genotypic compatibility in relation to row ratio in the intercropping of linseed (Linum usitatissimum) and gram (Cicer arietinum) under rainfed conditions - MISHRA, J P; ALI, MASOOD; ARYA, R L (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted during 1998-2000 at Kanpur to explore the best co,patible genotype and planting pattern for gram or chickpea (Cicer arietinum L.) + linseed (Linum usitatissimum L.) under rainfed conditions. Three genotypes, viz’BG 256’, KPG, 59’ and KWR 108’ of gram were intercropped with ’Neelam’ linseed under 2:1, 4:2 and 6:2 row arrangement (Chickpea : linseed) in replacement systems. ’KWR 108’ gram gave the highest seed yield of 2 406 kg/ha in its sole stand, registering an advantage of 403 and 484 kg/ha over ’KPG 59’ and ’BG 256’ respectively. However, in intercropping, BG 256’ proved more compatible than ’KPG 59’ and ’KWR 108’. The highest productivity of 2 601 kg/ha (Chickpea equivalent) was noticed in ’BG 256’ + ’Neelam’ under 6:2 planting pattern. A planting pattern of 6:2 row arrangement was most promising. The monetary return and benefit: cost ratio were also highest in the same combination. The highest monetary advantage (Rs 6 253/ha) and income-equivalent ratio (1.57) were found in ’BG 256’ + ’Neelam under 6:2 planting pattern, indicating the superiortiy of the system to others. Higher land -equivalent ratio and area-time equivalent ratio in the combination revealed efficient utilization of land space and time. Linseed showed more advantage in intercropping, having higher aggressivity and relative crowing coefficient. The higher competition ratio of linseed showed its more copetitivencess in the system.